Intensidade luminosa e exclusão da radiação UV na produção de Curcuma longa L. e purificação magnética de curcuminoides - Ferreira, Maria Izabela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Curcuma longa L. is a monocot of Zingiberaceae family. It is an important source of curcuminoids and its productivity differs significantly in different agro-climatic conditions. In this study we investigate the effects of light intensity levels and exclusion of solar UV radiation during different stages of the C. longa development on the content and yield of curcuminoids. We also studed the ecophysiological performance, biomass production, enzymatic activity, the level of polyamines and total phenols of these plants during cultivation. In addition, we proposed the optimization of curcuminoids purification method with magnetic nanoparticles called Surface Active maghemite Nanoparticles (SAMNs). The The experimental design was completely randomized with five light levels and four harvests, in a split plot in time, with five replicates of eight plants. Light levels were anti-UV polyethylene, full sun, 30 %, 50 % and 70 % of shading and harvest times were 65, 128, 174, and 203 days after planting (DAP) corresponding to January, April, May, and June 2013. The experiment was conducted in a experimental farm of Agronomic Sciences College, Universidade Estadual Paulista - UNESP, Botucatu - SP, in São Manuel - SP (22o46'0, 571 "S and 48o34'11, 32" W, 744 meters). It was observed that photosynthetic efficiency was higher in plants grown under UV exclusion throughout the growing season and this hight CO2 assimilation (A) reflected in significantly higher dry rhizomes and leaves biomass. At the end of the crop cycle total phenols content (TP), peroxidase (POD) and L-phenylalanine ammonia-lyase (PAL) activity increased with decreased exposure to light and under UV exclusion. The Spm content was higher in rhizomes of the plant exposed to full sun, Put levels were higher under UV exclusion and curcumin content remained unaltered. Remarkably, the UV exclusion led to higher CO2 net assimilation, biomass production and consequently, a notable 44,63 % higher total curcuminoid yield was observed, comparing with full sun plants. However the higher curcuminoid content was obtained at 65 DAP, under 70 % shading. This is interesting for the purification process, since at this developmental stage, the biomass is reduced and curcuminoid content is limited. The curcuminoids purification process with magnetic nanoparticles (SAMNs) has been optimized considering the influence of polarity of the solvent and the concentration of nanoparticles, leading to a yield of 69.7 mg curcuminoids g-1 of C. longa powder rhizome, a increase of 17.6 times, compared to the previously reported protocol, leading to the recovery of> 98 % curcuminoids and providing real possibilities for competitive industrial production of curcuminoids.

Curcuma longa L. is a monocot of Zingiberaceae family. It is an important source of curcuminoids and its productivity differs significantly in different agro-climatic conditions. In this study we investigate the effects of light intensity levels and exclusion of solar UV radiation during different stages of the C. longa development on the content and yield of curcuminoids. We also studed the ecophysiological performance, biomass production, enzymatic activity, the level of polyamines and total phenols of these plants during cultivation. In addition, we proposed the optimization of curcuminoids purification method with magnetic nanoparticles called Surface Active maghemite Nanoparticles (SAMNs). The The experimental design was completely randomized with five light levels and four harvests, in a split plot in time, with five replicates of eight plants. Light levels were anti-UV polyethylene, full sun, 30 %, 50 % and 70 % of shading and harvest times were 65, 128, 174, and 203 days after planting (DAP) corresponding to January, April, May, and June 2013. The experiment was conducted in a experimental farm of Agronomic Sciences College, Universidade Estadual Paulista - UNESP, Botucatu - SP, in São Manuel - SP (22º46'0, 571 "S and 48º34'11, 32" W, 744 meters). It was observed that photosynthetic efficiency was higher in plants grown under UV exclusion throughout the growing season and this hight CO2 assimilation (A) reflected in significantly higher dry rhizomes and leaves biomass. At the end of the crop cycle total phenols content (TP), peroxidase (POD) and L-phenylalanine ammonia-lyase (PAL) activity increased with decreased exposure to light and under UV exclusion. The Spm content was higher in rhizomes of the plant exposed to full sun, Put levels were higher under UV exclusion and curcumin content remained unaltered. Remarkably, the UV exclusion led to higher CO2 net assimilation, biomass production and consequently, a notable 44,63 % higher total curcuminoid yield was observed, comparing with full sun plants. However the higher curcuminoid content was obtained at 65 DAP, under 70 % shading. This is interesting for the purification process, since at this developmental stage, the biomass is reduced and curcuminoid content is limited. The curcuminoids purification process with magnetic nanoparticles (SAMNs) has been optimized considering the influence of polarity of the solvent and the concentration of nanoparticles, leading to a yield of 69.7 mg curcuminoids g-1 of C. longa powder rhizome, a increase of 17.6 times, compared to the previously reported protocol, leading to the recovery of> 98 % curcuminoids and providing real possibilities for competitive industrial production of curcuminoids.
Light intensity and uv exclusion in Curcuma longa L. production and magnetic curcuminoids purification
Keywords: Açafrão-da-terra; Fotossíntese; Nanopartículas; Compostos bioativos; Turmeric; Photosynthesis; Nanoparticles; Bioactive compounds; HPLC